Dampak Pengendalian pH Menggunakan Asam Asetat terhadap Sifat Mekanik dan Stabilitas Derajat Putih pada Kain Rajut Poliester - Ratih Kurniasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the effect of acetic acid-based pH adjustment on the mechanical properties and whiteness stability of polyester knitted fabrics. The method employed was an experimental approach using varying acetic acid concentrations (0–12%) to generate different pH conditions, followed by testing fabric pH, bursting strength, and phenolic yellowing according to AATCC, ASTM, and ISO standards. The results showed that increasing acetic acid concentration significantly reduced fabric pH. Lower pH conditions improved whiteness stability by reducing yellowing tendency; however, excessive acidity led to decreased mechanical strength. The relationship among pH, mechanical strength, and aesthetic quality exhibited a non-linear pattern with a trade-off between parameters. In conclusion, an optimum pH range was identified to balance mechanical performance and whiteness stability, providing potential contributions to process optimization and quality improvement in polyester textile finishing. Keywords: Acetic Acid, Bursting Strength, pH Adjustment, Polyester Knitted Fabric, Whiteness Stability